The tradition of markobar in mangalap boru "Picking a Bride" as advice for the women mental health in mandailing wedding ceremony - Tutiariani Nasution; Robert Sibarani; Syahron Lubis; Eddy Setia (Elsevier, 2021)
Objective: The study was conducted to explain the role of markobar (speech) in mangalap boru toward the bride (specifically) and women (generally) mental health in Mandailingnese. This study is concerned with explaining the phenomenon of using language used to console and strengthen the bride who will move into the groom's house. Methods: This study used the ethnography model. The data were taken using a recording, interview, and observation. The steps in markobar of mangalap boru were analyzed based on its structure and explaining the speech that consists of advice for the bride. Results: Markobar in mangalap boru produced the utterances to advise the bride to face her new situation with her groom's big family. The speech consists of an introduction by telling the steps of knowing the bride. It was then continued by a speech of accepting the bride to the grooms' big family and advice from both sides. It is covered by giving speeches of the bride's family's requests to take care of their daughter and promise from the groom's family. Conclusion: Tradition markobar in mangalap boru affected the bride's mental health to release her life custom with her family and move forward with her new husband. The advice pieces in markobar strengthen her spirit and mental to accept the new situation and adapt it sincerely. The language used and performance in delivering markobar is Mandailing local wisdom that should be maintained toward an agreed life system in Mandailingnese.